Research on the visual elements of augmented reality assembly processes - Wang Li; Junfeng Wang; Sichen Jiao; Meng Wang; Shiqi Li (Virtual Reality & Intelligent Hardware, 2019)
Background: To solve the problem of visualization in augmented reality (AR), for assembly process information, we report here on our study into the composition of AR assembly process information. Methods: Our work led us to classify the visual elements of assembly processes into six categories, and after looking further into visual element expression characteristics used in assembly process information in the AR environment, standard assembly process elements have been identified and visual element layout principles studied. Conclusion: Typical visualization elements have been presented, using an AR-based assembly instruction system. Keywords: Augmented reality, Visual element, Process information, Assembly guidance